Respuesta :

Answer:

  x = -9/2 or -5/3

Step-by-step explanation:

The given equation is recognizable as a quadratic in the expression (2x+4). It may be more easily solved by substituting a variable for that expression.

__

setup

Let z = 2x+4. Then the equation becomes ...

  6z² = z +2

  6z^2 -z -2 = 0

solution to the quadratic

This equation can be factored by finding factors of (6)(-2) that total -1.

  (6z -4)(6z +3)/6 = 0

  (3z -2)(2z +1) = 0 . . . . . eliminate the fraction

The values of z that make these factors zero are ...

  3z -2 = 0   ⇒   z = 2/3

  2z +1 = 0   ⇒   z = -1/2

values of x

The relation between x and z tells us ...

  z = 2x +4

  (z -4)/2 = x

For the values of z we have, the corresponding x-values are ...

  z = 2/3   ⇒   (2/3 -4)/2 = x = -10/6 = -5/3

  z = -1/2   ⇒   (-1/2 -4)/2 = x = -9/4

Solutions to the equation are x=-9/4 and x=-5/3.

_____

Additional comment

Alternatively, the equation could have been expanded to standard form and then factored.

  6(4x² +16x +16) = 2x +6

  24x² +94x +90 = 0 . . . . put in standard form

  12x² +47x +45 = 0 . . . . factor out 2

  (4x +9)(3x +5) = 0 . . . . factor (judged harder than the above factoring)

ACCESS MORE